Customary Law Problems Against the Application of Santet from the Perspective of Indonesian Islamic Law - Mansur, Mochamad; Lesmana, Ryan Fachryan; Mangar, Irma (Journal of Development Research, 2025)
In the modern era and the super sophisticated era like today, there are still many people who believe and use the so-called witchcraft and the increasing popularity of mass media, both print and electronic, related to it. This is because materialistic culture has distanced some of humanity from religious values and norms. This research uses a descriptive method of analysis, namely by collecting, studying, analyzing and interpreting and explaining data related to Customary Law Problems in the Application of Santet Reviewed from Indonesian Islamic Law, the belief in the existence of supernatural powers in Indonesia is a culture that has existed for a long time from the community. The belief in supernatural powers has caused many paranormal practices or shamans in people's lives, the results of this study show that in a community dominated by certain beliefs and religions, the members are not only residents of the village unit according to the law, but also traditional indigenous people and religious citizens who adhere to their respective beliefs, then it is clear that in customary law there is no room for magic acts (Santet).